Application of Pineapple Slicer Tool as Appropriate Technology for Pineapple Chips Production and Calculation of Cost of Production to Increase Business Productivity - Sabda Dian Nurani Siahaan; Lenti Susanna Saragih; Siti Ulgari; Haryani Pratiwi Sitompul (Jurnal Pengabdian Masyarakat Formosa, 2023)
The partners in this Community Partnership Program (PKM) activity are the Maju Tani Group located in Boangmanalu Village, Salak District, Pakpak Bharat Regency. The problems found in partners are in the production sector, namely the size of the pineapple chips is irregular and the partners do not understand how to determine the selling price of the product. Improvements to the pineapple chip business need to be done to improve and maintain business continuity. Handling of this problem is also important because the Maju Tani group are farmer-based entrepreneurs who need to be equipped with business knowledge so they can advance their business. The solution offered to overcome this problem is to provide a pineapple slicer tool and provide business financial management training. The method of implementing this activity is training and mentoring.